Building Smart Tourism Through Business Intelligence: Social Media Analytics in the Indonesian Travel Market - Moch Dhisa Rizky Madani; Ramdan Saeful Qoyim (Trasearch (Training, Research and Academy Society, 2025)
The tourism industry in Indonesia is increasingly influenced by digital transformation, particularly through the integration of Business Intelligence (BI) systems. Despite the growing volume of social media interactions in the travel sector, many Indonesian tourism enterprises struggle to convert these data into actionable insights. This study aims to explore how social media analytics, as a subset of BI, contributes to the development of smart tourism in Indonesia. Employing a qualitative exploratory design, the research collected primary data through semi-structured interviews with twelve key stakeholders, including travel agency managers, marketing specialists, and data analysts. Secondary data were also drawn from BI dashboards and social media analytics tools such as Facebook Insights and Twitter Analytics. Thematic analysis revealed five key findings: (1) social media platforms provide real-time insights into tourist behavior; (2) BI systems support strategic planning and operational alignment; (3) personalization and customer engagement are enhanced through data-driven segmentation; (4) challenges persist in technical capacity, infrastructure, and data ethics; and (5) localization of BI tools is crucial for accurate and culturally sensitive analysis. The study contributes both theoretically and practically by contextualizing BI adoption within the Indonesian tourism industry, highlighting its strategic value and identifying barriers to implementation. These findings support the advancement of smart tourism initiatives and offer practical guidance for travel operators, policymakers, and platform developers. Future research is encouraged to adopt mixed-methods approaches and evaluate BI impacts on organizational performance across diverse tourism settings.